Dose-Response Relationships Between Gonadal Steroids and Bone, Body Composition, and Sexual Function in Aging Men - Finkelstein, Joel S (J Clin Endocrinol Metab, 2020)
CONTEXT: Most labs set the lower limit of normal for testosterone at the 2.5th percentile of values in young or age-matched men, an approach that does not consider the physiologic changes associated with various testosterone concentrations. OBJECTIVE: To characterize the dose-response relationships between gonadal steroid concentrations and measures regulated by gonadal steroids in older men. DESIGN, PARTICIPANTS, AND INTERVENTION: 177 men aged 60 to 80 were randomly assigned to receive goserelin acetate plus either 0 (placebo), 1.25, 2.5, 5, or 10 grams of a 1% testosterone gel daily for 16 weeks or placebos for both medications (controls). PRIMARY OUTCOMES: Changes in serum C-telopeptide (CTX), total body fat by dual energy X-ray absorptiometry, and self-reported sexual desire. RESULTS: Clear relationships between the testosterone dosage (or the resulting testosterone levels) and a variety of outcome measures were observed. Changes in serum CTX exceeded changes in the controls in men whose testosterone levels were 0 to 99, 100 to 199, 200 to 299, or 300 to 499 ng/dL, whereas increases in total body fat, subcutaneous fat, and thigh fat exceeded controls when testosterone levels were 0 to 99 or 100 to 199 ng/dL. Sexual desire and erectile function were indistinguishable from controls until testosterone levels were <100 ng/dL. CONCLUSION: Changes in measures of bone resorption, body fat, and sexual function begin at a variety of testosterone concentrations with many outcome measures remaining stable until testosterone levels are well below the stated normal ranges. In light of this variation, novel approaches for establishing the normal range for testosterone are needed.